Breast Cancer Subtypes Based on Hypoxia-Related Gene Sets Identify Potential Therapeutic Agents - Xiong, Zhenchong; Huang, Weiling; Zhong, Wenjing; Fu, Jianchang; Feng, Jikun; Wang, Xi; Ling, Feihai (Frontiers in Molecular Biosciences, 2022)
Purpose: The hypoxic tumor microenvironment was reported to be involved in different tumorigenesis mechanisms of breast cancer(BC). We aimed to establish a hypoxia-related gene signature to identify a new BC subtype through the clustering analysis and explore potential compounds targeting the BC subtypes. Methods: Gene expression data and clinical features of BC and adjacent non-tumor tissues were downloaded from the Cancer Genome Atlas-Breast cancer (TCGA-BRCA) database. We comprehensively revealed the activity changes of Gene Ontology (GO) biological processes (BP) gene sets in BC by gene set variation analysis (GSVA), and identified three hypoxia-related BC subtypes. We then matched the differentially expressed gene profile of each subtype with the gene profile in CMap database to identify the potential agents targeting the BC subtypes. Results: 562 of Gene Ontology biological processes gene sets were significantly correlated with hypoxia score in breast cancer. 969 BC patients were clustered into three subtypes based on the enrichment score of hypoxia-associated gene sets. Subtype 1 patients displayed better survival than subtype 2 and 3. KEGG pathway enrichment analysis of each subtype was performed based on the unique differential expression genes profile. In subtype 1, the up-regulated genes associated with lipid and amino acid metabolism regulation; in subtype 2, the up-regulated genes associated with metabolic energy regulation, while in subtype 3, the up-regulated genes associated with apoptosis, and protein process. Using the CMap database, 55, 111 and 63 compounds were identified targeting subtype 1, 2 and 3, respectively. Conclusions: In this study, novel hypoxia-related subtypes were developed for patients with BC. Biological processes associated with differential expression genes profile and potential therapeutic target compounds were identified in each subtype. The new classification may provide a better understanding of the role of hypoxia in breast cancer and more individualized treatment for patients.